Gastric remnant cancer: A distinct entity or simply another proximal gastric cancer?. Issue 8 (29th October 2015) - Tran, Thuy B.; Hatzaras, Ioannis; Worhunsky, David J.; Vitiello, Gerardo A.; Squires, Malcolm Hart; Jin, Linda X.; Spolverato, Gaya; Votanopoulos, Konstantinos I.; Schmidt, Carl; Weber, Sharon; Bloomston, Mark; Cho, Clifford S.; et al.
Abstract : Background: The purpose of this study was to compare outcomes following resection of gastric remnant (GRC) and conventional gastric cancer. Methods: Patients who underwent resection for gastric cancer in 8 academic institutions from 2000–2012 were evaluated to compare morbidity, mortality, and survival based on history of prior gastrectomy. Results: Of the 979 patients who underwent gastrectomy with curative‐intent during the 12‐year study period, 55 patients (5.8%) presented with GRC and 924 patients (94.4%) presented with conventional gastric cancer. Patients with GRC were slightly older (median 69 vs. 66 years). GRC was associated with higher rates of complication (56% vs. 41%, P  = 0.028), longer operative times (301 vs. 237 min, P  < 0.001), higher intraoperative blood loss (300 vs. 200 ml, P  = 0.012), and greater need for blood transfusion (43% vs. 23%, P  = 0.001). There were no significant differences in 30‐day (3.6% vs. 4%) or 90‐day mortality (9% vs. 8%) between the two groups. Overall survival rates were similar between GRC and conventional gastric cancer (5‐year 20.3% vs. 38.6%, P  = 0.446). Multivariate analysis revealed that history of gastrectomy was not predictive of survival while established predictors (older age, advanced T‐stage, nodal involvement, blood transfusion, multivisceral resection, and any complication) were associated with poor survival. Conclusions: Despite higher morbidity, prognosis after resection of gastric remnant cancer is similar to conventional gastric cancer. J. Surg. Oncol. 2015;112:877–882 . © 2015 Wiley Periodicals, Inc.